Retrospective evaluation of stabbing cases in Elazig - Dulger, H.E. (My University, 1994)
In Elazig, one hundred twenty five person have been stabbed during period 1990, 1991 and 1992. Of the cases 94.4 % (118) were male. The mean age for the cases was 25.2. Chest (39 persons - 32.8 %) and abdomen (36 persons - 30.3 %) were mostly wounded parts of the body. The lives of forty eight person threatened. Of these cases 24 had penetrating stab wounds to the abdomen, 19 to the chest, and 5 to both the abdomen and chest. Small intestine and colon were the most damaged parts in the organ lesions. The forensic reports of the above cases were given by four hospitals in the city.
KESICI-DELICI ALET YARALANMALARININ RETROSPEKTIF INCELENMESI
Keywords: Forensic reports; Stab wounds